ANALISIS PENGARUH LITERASI KEUANGAN SYARI’AH DAN RELIGIUSITAS TERHADAP MINAT BERTRANSAKSI PADA BANK SYARIAH DALAM PERSPEKTIF HUKUM EKONOMI ISLAM - Moch. Uzeir Mustaqfirin; Muhamad Ali Tamrin; Muhamad Nuruzzaman (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2025)
This study aims to determine the effect of Islamic financial literacy and religiosity on student interest in transactions in Islamic banks, with a case study of HES study programme students at the IAIFA Kediri campus. Using quantitative methods, this study tests the hypothesis through partial and simultaneous analysis. The results of simultaneous testing show that Islamic financial literacy and religiosity together have a significant effect on interest in transactions in Islamic banks. However, partial analysis reveals that Islamic financial literacy does not have a significant effect on transaction interest. In contrast, religiosity is proven to have a positive and significant effect on transaction interest. But the percentage contribution of the Islamic financial literacy variable shows a very small, almost insignificant contribution to the dependent variable. Only about 0.42% of the variation in the dependent variable can be explained by the Islamic financial literacy variable. Meanwhile, religiosity makes a very large contribution to the dependent variable. About 99.58% of the variation in the dependent variable can be explained by the religiosity variable. Thus it can be concluded that Islamic financial literacy and religiosity simultaneously contribute positively in shaping interest in transactions in Islamic banks. This finding confirms the urgency of Islamic financial institutions in improving sharia literacy education and economic da'wah programmes so that the objectives of Islamic economic law (justice and welfare) are more optimal.